JOURNAL OF GOVERNMENT & POLITICS : The Realness Discourse of a Political Leader : A Komunikasi Berasa Perspective - Bambang Sukma Wijaya (FISIPOL UMY, 2016)
This article examines the communication style of the former Governover of Jakarta and presidential candidate during the 2014 Indonesian election.